Pengaruh Electronic Word of Mouth (E-WOM) terhadap Brand Awareness Produk Scarlett di Media Sosial TikTok - Muthia Aulia Pradipta; Qoryna Noer Seyma; Mentari Anugrah Imsa; Asep Soegiarto; Menati Fajar Rizki (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
Scarlett, a local beauty brand, has achieved significant success in its marketing efforts, particularly through the strategic exploitation of electronic word-of-mouth (e-WOM) on the social media platform TikTok. By leveraging reviews, testimonials, and recommendations from users and influencers, Scarlett drives interactions that increase brand awareness. In this context, e-WOM serves as a strategic communication instrument that can be utilized by PR practitioners to foster good brand perception. For this purpose, a quantitative approach was used, which involved distributing a questionnaire to 100 TikTok users who follow Scarlett’s official account. The findings of the current study prove that the dimensions of e-WOM, specifically intensity, opinion, and content, have a significant influence on Scarlett’s brand awareness. The findings of this study prove that the integration of social media and E-WOM (Electronic Word-of-Mouth) in PR strategies is a crucial factor in strengthening a brand’s presence in the contemporary digital landscape, which is characterized by increasing competition.